2021
DOI: 10.21037/apm-21-2597
|View full text |Cite
|
Sign up to set email alerts
|

A randomized clinical trial: optimal strategies of paravertebral nerve block combined with general anesthesia for postoperative analgesia in patients undergoing lobectomy: a comparison of the effects of different approaches for serratus anterior plane block

Abstract: Background: To observe the analgesic effect of different ultrasound-guided methods of serratus anterior plane block (SAPB) after surgery in patients who have undergone thoracoscopic lobectomy with general anesthesia combined with thoracic paravertebral nerve block.Methods: A total of 120 patients aged 18-65 years old scheduled for video-assisted thoracoscopic surgery (VATS) were selected. Patients were randomly divided into 3 groups: patient-controlled intravenous analgesia (PCIA) group, serratus anterior plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 15 publications
0
16
1
Order By: Relevance
“…Er, et al reported that compared with GA, SAPB was associated with shorter hospital stay, as it was associated with improved quality of recovery scores by reducing early postoperative pain scores. [33] Nevertheless, the reduction in length of PACU or hospital stay observed in our study did not seem to be encouraging enough for clinical practice. As to the postoperative complications, we could not draw any conclusion due to small sample size.…”
Section: Disscussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…Er, et al reported that compared with GA, SAPB was associated with shorter hospital stay, as it was associated with improved quality of recovery scores by reducing early postoperative pain scores. [33] Nevertheless, the reduction in length of PACU or hospital stay observed in our study did not seem to be encouraging enough for clinical practice. As to the postoperative complications, we could not draw any conclusion due to small sample size.…”
Section: Disscussioncontrasting
confidence: 64%
“…[12,13] Regional blocks were believed to be potential to promote early mobilization in patients after VATs since it could reduce the incidence of moderate to severe pain in the early postoperative period. [10,11,28,33] It was reported that the use of regional block reduced postoperative opioid consumption and prolonged the time-to-rst rescue analgesic in patients after VATs compared with those who did not receive regional blocks. [14,24,33,34] Recent studies compared the analgesic effects of TEA, TPVB, and SAPB in patients after VATs and found that they were comparable in terms of opioid-sparing effects and postoperative pain scores.…”
Section: Disscussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table I illustrates the included studies, the number of participants and the data nodes involved for seven different outcome events. Of the included studies, 28 RCTs [ 10 – 37 ] reported opioid consumption; from 49 RCTs [ 10 , 12 , 14 – 17 , 19 , 21 – 26 , 28 – 30 , 32 , 34 – 65 ], 41 RCTs [ 10 , 12 , 15 17 , 19 , 21 – 26 , 28 , 29 , 31 , 32 , 34 – 37 , 39 – 43 , 45 – 49 , 51 , 54 , 56 , 57 , 59 – 65 ], and 49 RCTs [ 10 , 12 , 14 – 17 , 19 26 , 28 – 32 , 34 – 46 , 48 53 , 55 – 63 , 65 , 66 ], we obtained pain scores for three postoperative time periods (early, midterm, and late); and 10 RCTs [ 10 , 16 , 20 , 21 , 25 , 28 , 32 , 35 , ...…”
Section: Resultsmentioning
confidence: 99%
“…Most studies applying single-shot techniques included only ASA I and II patients [ 38 , 54 , 55 , 65 ] and uniportal VATS techniques [ 48 , 71 ] possibly creating a selection bias of patients with an advantage in rapid recovery and early discharge. Moreover, single-shot unilateral techniques were also accompanied by adjuvants such as dexmedetomidine, nalbuphine and dexamethasone [ 55 , 65 , 78 ] as well as experimental studies using liposomal bupivacaine [ 67 , 68 ], thereby extending the efficacy of single-shot blocks promoting ERATS. All factors taken into consideration, not only the applied analgesic technique has an impact on LOS, but the tendency to follow ERATS protocols and studies focusing on pain control, create a clear advantage resulting in early hospital discharge.…”
Section: Discussionmentioning
confidence: 99%